Impact of Teachers’ Workload on Teaching Performance of High School Teachers in Isabela: Basis for Policy Recommendation in DepEd - Saculles, Rodolfo; Batoon, Nerissa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between teacher workload, particularly ancillary tasks, and teaching performance among public secondary school teachers in Isabela. Anchored on a conceptual framework linking teacher profile, extent of ancillary tasks, and teaching performance with intervening challenges such as time constraints and stress, the study employed a quantitative descriptive-correlational design. A total of 378 teachers were selected through purposive sampling and complete enumeration from selected schools. Data were collected using a validated and reliable questionnaire covering demographic profile, ancillary task involvement, perceived burden, teaching performance based on the Philippine Professional Standards for Teachers (PPST), and challenges encountered. Statistical analyses included frequency, percentage, weighted mean, Kruskal-Wallis H test, and Pearson correlation coefficient. Findings revealed that teachers are highly involved in curriculum-related ancillary tasks, moderately involved in school management, and minimally engaged in inter-agency functions, with an uneven distribution of responsibilities. While ancillary tasks were generally perceived as slightly burdensome, specific roles such as class advisership and canteen management were considered more demanding. Despite these responsibilities, teachers demonstrated a very high level of teaching performance across all domains. However, they experienced significant challenges in balancing instructional and non-instructional duties, including time constraints, stress, and reduced instructional focus. The relationship between ancillary tasks and teaching performance was found to be weak to moderate but generally significant, with student-centered and leadership-related tasks contributing positively, while routine administrative tasks showed minimal impact. Differences in task involvement were also observed across sex, age, educational attainment, and years of service. The study concludes that although teachers maintain high instructional effectiveness, workload pressures and uneven task distribution pose challenges to sustainability in teaching performance. It recommends rationalizing ancillary tasks, improving workload distribution, strengthening support systems, and enhancing professional development. This study supports SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth) by addressing instructional quality and teacher working conditions. It contributes to educational, institutional, and socio-economic sustainability by promoting equitable workload management, teacher well-being, and improved instructional effectiveness.